Association of missense variant DCLRE1B rs3761936 with breast and cervical cancer risk—A case-control study - Sarah Jafrin; Md. Abdul Aziz; Md Abdul Barek; Md. Sharif Reza; Nura Ershad Naznin; Mohammad Safiqul Islam (PLoS ONE, 2025)
Background Overexpression of rs3761936 of DCLRE1B gene has been observed in both breast cancer and cervical cancer patients. To justify the association of this polymorphism with these cancers, we performed this case-control study. Method A total of 245 cancer patients and 108 healthy controls participated in the research. An efficient T-ARMS PCR method was used for genotyping. Results The cancer patients showed higher mutant allele frequency compared to the controls. Mutant allele carrier breast cancer patients showed significantly increased risk in four genetic models, including additive model 1 (TC vs. TT: OR=2.31, 95% CI = 1.33–3.99, p-value = 0.0028), additive model 2 (CC vs. TT: OR=3.93, 95% CI = 1.36–11.38, p-value = 0.0116), dominant model (TC + CC vs. TT: OR=2.52, 95% CI = 1.50–4.25, p-value = 0.0005), and over-dominant model (TC vs. TT + CC: OR=1.93, 95% CI = 1.13–3.28, p-value = 0.0152). The allele frequency analysis showed that mutant allele C carriers among breast cancer patients had a significantly higher risk than the wild type T allele carriers (C vs. T: OR=2.15, 95% CI = 1.41–3.26, p-value = 0.0003). Likewise, the cervical cancer patients showed significant risk in three genetic models, including additive model 1 (TC vs. TT: OR=1.80, 95% CI = 1.01–3.20, p-value = 0.0444), additive model 2 (CC vs. TT: OR=3.17, 95% CI = 1.05–9.55, p-value = 0.0403), and dominant model (TC + CC vs. TT: OR=1.98, 95% CI = 1.15–3.41, p-value = 0.0138). The mutant allele C carriers had a significantly higher risk than the wild-type T allele carriers (C vs. T: OR=1.84, 95% CI = 1.19–2.85, p-value = 0.0065). Conclusion DCLRE1B rs3761936 is strongly associated with breast cancer and cervical cancer risk in Bangladeshi women.